posted by .

1. Simplify 49^3/2.

2. Simplify 5^ãx^25y^125.

3. When the polynomial 5x - 2x + 8x^2 - 7 is written in standard form, what is the leading coefficient?

4. Classify the polynomial 5x^2 + 9x + 1 according to tis degree and number of terms.

5. Genie has 100 feet of fence with which to make a rectangular cage for her rabbit. If she uses the wall of her house as one side, the area of the cage in square feet is given by the polynomial -2x^2 + 100w, where w is the width of the cage in feet. What is the area of the cage if the width is 15 feet?

6. Add (5x^2 - 2x + 9) + (2x^2 - 4).

My answer: 7x^4 - 2x + 5?

7. Subtract (10a^2 - 6a) - (7a^2 - 8a).

8. Multiply (-5rs^4)(3r^5s^2).

9. (3x - 4)^2

My answer: 6x^2 - 24x + 8?

10. (2x + 4)(2x - 4)

• Algebra 1 Answer Check -

1. correct if you meant 49^(3/2)
The way you typed it --- 117649/2

3. the leading term in standard notation would be 8x^2

4. correct

5. the x is undefined in your problem

6. 7x^2 - 2x + 5, the exponent is not affected when adding like terms

7. 3a^ + 2a

8. correct

9. 6x^2 - 24x + 16 , 4 x 4 = 16 not 8

10. 4x^2 - 16

looks like somebody has some serious studying to do.

• Algebra 1 Answer Check -

1.

If 49^3/2 mean 49 ( 3 / 2 ) then:

49 ( 3 / 2 ) = [ ( 49 ) ^ 3 ] ^ ( 1 / 2 ) =

[ ( 49 ) ^ ( 1 / 2) ] ^ 3 =

sqrt ( 49 ) ^ 3 =

7 ^ 3 = 343

Correct

2. What is 5^ãx^25y^125 ?

3.

5 x - 2 x + 8 x ^ 2 - 7 =

8 x ^ 2 + 3 x - 7

In a polynomial, the coefficient of the term with the highest degree is called the leading coefficient.

So the leading coefficient = 8

4.

Correct

5.

x = the length of the side parallel to the building

w = the width of the cage

x + 2 w = 100

Subtract 2 w to both sides

x + 2 w - 2 w = 100 - 2 w

x = 100 - 2 w

Area = length * width

A = x * w =

( 100 - 2 w ) * w =

100 w - 2 w ^ 2 =

- 2 w ^ 2 + 100 w

NOT ( - 2 x ^ 2 + 100 w )

A = - 2 w ^ 2 + 100 w

= - 2 * 15 ^ 2 + 100 * 15 =

- 2 * 225 + 1500 =

-450 + 1500 =

1050 ft ^ 2

6.

( 5 x ^ 2 - 2 x + 9 ) + ( 2 x ^ 2 - 4 ) =

5 x ^ 2 - 2 x + 9 + 2 x ^ 2 - 4 =

5 x ^ 2 + 2 x ^ 2 - 2 x + 9 - 4 =

7 x ^ 2 - 2 x + 5

7.

( 10 a ^ 2 - 6 a ) - ( 7 a ^ 2 - 8 a ) =

10 a ^ 2 - 6 a - 7 a ^ 2 - ( - 8 a ) =

10 a ^ 2 - 6 a - 7 a ^ 2 + 8 a =

10 a ^ 2 - 7 a ^ 2 - 6 a + 8 a =

3 a ^ 2 + 2 a

8.

Correct

9.

( a - b ) ^ 2 = a ^ 2 - 2 * a * b + b ^ 2

( 3 x - 4 ) ^ 2 =

( 3 x ) ^ 2 - 2 * 3 x * 4 + 4 ^ 2 =

9 x ^ 2 - 6 x * 4 + 16 =

9 x ^ 2 - 24 x + 16

10.

( 2 x + 4 ) * ( 2 x - 4 ) =

2 x * 2 x + 2x * 4 - 4 * 2 x - 4 * 4 =

4 x ^ 2 + 8 x - 8 x - 16 =

4 x ^ 2 - 16

OR

( a + b ) * ( a - b ) = a ^ 2 - b ^ 2

( 2 x + 4 ) * ( 2 x - 4 ) =

( 2 x ) ^ 2 - 4 ^ 2 =

4 x ^ 2 - 16

Similar Questions

Find the length of the 3rd side of each right triangle. 1. 8^2+15^2=c^2 Answer: c=17 2. 5^2+b^2=13^2 Answer: b=12 3. 9^2+13^2=c^2 Answer: c~15.81 Simplify. Assume that all variables are nonnegative. { this means square root 4. {12 …

Perform the indicated operations and simplify the result. Leave your answer in factored form. 1) x/16 - 1/x all over 1 + 4/x A) x+4/16 B) x-4/16 C) 16/x+4 D) 16/x-4 E) -16/x+4 I chose answer C. I saw this as x^2-16/ x+4. Multiply the …

Please check these answers. Multiply -7(2a2 -4) = -14a2 + 28 Multiply 0.5(a + b -5) = 0.5a + 0.5b - 2.5 Factor bx - by + bz = b(x - y + z) Combine like terms (simplify) 12x + 4 - 11y - 6x - 9 - y = 6x - 12y - 5 Evaluate the expression …
4. Algebra

Can you please check my work? You have helped other students I know. Thank you:) Multiply -7(2a2 -4) = -14a2 + 28 Multiply 0.5(a + b -5) = 0.5a + 0.5b - 2.5 Factor bx - by + bz = b(x - y + z) Combine like terms (simplify) 12x + 4 -
5. math-check

I have solved the following questions, let me know if they are correct, thanks. 1. Simplify, and write in the base of 3: (9^x . 3^4x)^2 answer: 3^12x 2. Differentiate and simplify a. y= 3x^4 - 4e^x + 8 answer: 4(3x^3 - e^x) b. y= (3 …
6. algebra 2

1.Simplify the difference. n^2 - lOn+24 9 / n^2 - 13n + 42 — 7 A. n-13/n-7 <<< B. n-4/n-7 C. n-13 2.Simplify the complex fraction. y-1/y^2+y-6/y-6/y+3 A.(y-1)(y-6)/(y+3)^2(y-2) B. y-1/(y-6)(y-2) C.(y-1)(y-6)/(y+3)(y-2)<<< …